2021
DOI: 10.12968/ijtr.2020.0070
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth in paediatric occupational therapy: a scoping review

Abstract: Background/Aims This study reviewed the use of telehealth in paediatric occupational therapy practice and its clinical outcomes over the past 20 years. Methods A scoping review following Arksey and O'Malley's five stages was undertaken using six databases and Google Scholar. The scoping review covered articles from January 2000 to April 2020. Results A total of 22 articles were reviewed. Most studies indicated positive outcomes of using telehealth in paediatric occupational therapy practice. Although there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…This finding also suggests the potential relevance of clinicians’ actual experience and that of their colleagues in their assessment of an innovation like video telehealth, particularly in the absence of published research studies 29 , 30 . In our related work, we found that while both users and non-users of video telehealth were comfortable using video telehealth for OT interventions, users expressed higher comfort ratings compared to non-users 20 .…”
Section: Discussionmentioning
confidence: 74%
“…This finding also suggests the potential relevance of clinicians’ actual experience and that of their colleagues in their assessment of an innovation like video telehealth, particularly in the absence of published research studies 29 , 30 . In our related work, we found that while both users and non-users of video telehealth were comfortable using video telehealth for OT interventions, users expressed higher comfort ratings compared to non-users 20 .…”
Section: Discussionmentioning
confidence: 74%
“…Internationally, different public health responses to the Covid‐19 pandemic were put in place, such as wearing face masks, social distancing, using hand sanitizer/hand washing, and getting vaccinated as means to combat the spread of Covid‐19. Doctors and allied health practitioners moved to using a remote model of health delivery using telehealth and telerehabilitation approaches (Önal et al, 2021 ). For children with special needs and learning problems, occupational therapy services prioritised a remote consultation model using telehealth and school‐based telerehabilitation approaches for school‐age children (Dahl‐Popolizio et al, 2020 ; Hermes et al, 2021 ).…”
Section: Health Responses To Covid‐19 Pandemicmentioning
confidence: 99%
“…Telehealth can assist with providing uninterrupted and accessible pediatric occupational therapy services, and some research indicates its efficacy (Cason et al, 2018; Figueiredo, 2019). However, telehealth is currently not a common approach used by occupational therapists in pediatrics, and the majority of studies examining this model were conducted to determine its feasibility in the United States (Önal et al, 2021). To measure the effectiveness of occupational therapy interventions, reliable and valid outcome assessment tests are needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, one may not assume that standard assessment measures can be applied effectively to telehealth (Durfee et al, 2007). Therefore, another important consideration for tele-evaluation is the need to determine which pediatric occupational therapy evaluations are suitable for telehealth, by examining the reliability and validity of occupational therapy assessments administered remotely (Jacobs et al, 2015; Önal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%